Upsetting the agenda: the clout of external focusing events in the European Council. (20th May 2015) - Alexandrova, Petya
Abstract: Focusing events are sudden, striking large-scale occurrences that attract political attention. However, not all potential focusing events appear on the agenda. Combining data from multiple sources, this study conducts an analysis of the determinants of prioritisation of external focusing events in the European Council over a period longer than two decades. The results demonstrate that decisions regarding the placement of crises on the agenda are underscored by exogenous (humanitarian) and endogenous (geopolitical interest) considerations. Those events with a higher likelihood of agenda access include manmade incidents (versus natural disasters), events with larger death tolls and crises in the neighbourhood. Stronger competition between potential focusing events across time and space reduces the chances of access. The level of attention each event receives depends on purely strategic interests. Focusing events in neighbouring countries gain a higher portion of attention, as do occurrences in states having a larger trade exchange with the European Union.